2016
DOI: 10.1007/s10639-016-9527-4
|View full text |Cite
|
Sign up to set email alerts
|

Learning density in Vanuatu high school with computer simulation: Influence of different levels of guidance

Abstract: International audienceThis paper presents a study on discovery learning of scientific concepts with the support of computer simulation. In particular, the paper will focus on the effect of the levels of guidance on students with a low degree of experience in informatics and educational technology. The first stage of this study was to identify the common misconceptions about density, starting from a literature review. Forty eight students (25 M and 23 F) from two high schools in Vanuatu were then involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Regarding to the inquiry cycle, there was no evidence that guidance was more efficient when providing in certain phases. In addition, the reviewed studies indicated that providing higher level of guidance with more detailed instruction or structure did not necessarily induce better knowledge acquisition nor inquiry performance (Blikstein et al, 2017; Moli et al, 2017; Wichmann & Timpe, 2015). This study identified three major factors that may shape the effectiveness of guidance in simulation‐based inquiry learning environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding to the inquiry cycle, there was no evidence that guidance was more efficient when providing in certain phases. In addition, the reviewed studies indicated that providing higher level of guidance with more detailed instruction or structure did not necessarily induce better knowledge acquisition nor inquiry performance (Blikstein et al, 2017; Moli et al, 2017; Wichmann & Timpe, 2015). This study identified three major factors that may shape the effectiveness of guidance in simulation‐based inquiry learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…Studies related to prompts are presented in Table A2. Moli et al (2017) compared how different levels of prompts affected students' conceptual understanding in a paired-up simulated inquiry-learning task. They found that although groups received paper-based concept probing questions (minimum guided group) or paper-based concept probing questions plus detailed instruction (maximum guided group) did not outperform the unguided group in knowledge acquisition, the maximum guided group had a more successful conceptual change than the other groups.…”
Section: Promptsmentioning
confidence: 99%
“…Thus, we conclude that CS in teaching is beneficial for students in learning the referred phenomena and theory. The effectiveness of learning with CS depends on the CI mode of CS (Araújo et al 2019a, b), the degree of task guidance (Moli et al 2017) and the mediation of the teacher with regard to guidance in exploring CS and the autonomy provided to students (Araújo et al 2019a, b). We conclude that autonomy with low guidance can be ineffective and that mediation with a lot of teacher intervention in the context of moderately guidance tasks can also reduce effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Psychologists and curricula designers have always strived for an effective instruction that would help students to assimilate ratio-concepts. Many researches focus on the organization of the learning process and advise: guided-inquiry based teaching (Almuntasheri et al, 2016;Moli et al, 2017); authentic investigative activities (Ben-Chaim, Keret & Ilany, 2012); development of students' argumentation (Chen et al, 2014). The aspects, which have been studied regarding the problem of teaching ratio vary greatly: strategies and rules that children use (Siegler & Chen, 2008), type of feedback they get, possibility to perform some experiments, etc.…”
Section: Problem Statementmentioning
confidence: 99%